PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) GUNA MENINGKATKAN KETERAMPILAN MENULIS TEKS PIDATO PADA MAHASISWA SEMESTER III JURUSAN PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Ida Ayu Md. Darmayanti; I Gd. Nurjaya; I Nengah Martha (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
The design of this study was a classroom action research design that was done by using two cycles. This study is aimed to find out the appropriate learning steps in the problem based learning method that can improve the creativity in writing speech text of the 3rd semester students in Indonesian Language Education Department. The subject of this study were the 3rd semester students in Indonesian Language Education Department. The data of this study were collected by using three instruments, they are observation, interview, and questionnaire. Besides, the result of this study are the effective learning steps related with the creativity in writing a speech text. Not only to improve the creativity in writing speech text for the college students, the appropriate learning steps in problem based learning method can also improve the learning activity of college students in the classroom. That improvement was proven by their responses which show that they are agree with the application of the problem based learning method. Thus, this study suggested the other researchers that observe this kind of topic to be able to research this kind of study from the other aspects.